A HOSPITALIDADE COMO FUNDAMENTO TEÓRICO-FILOSÓFICO DE UMA CIDADANIA COSMOPOLITA PARA REFUGIADOS: HOSPITALITY AS A THEORETICAL-PHILOSOPHICAL FOUNDATION OF A COSMOPOLITE CITIZENSHIP FOR REFUGEES (Revista Direitos Humanos e Democracia, 2021)
The presente paper, starting from a philosophical tetrad, as a theoretical parameter, aims to investigate the ethical challenge of welcoming refugees and to analyze the fundamentals and complexities that involve hospitality, with the purpose of dimensioning philosophical alternatives viable for the consolidation of solidarity from the re-reading of the concept of human person and multicultural coexistence. To this end, it developed a comparative analysis of the Kant’s cosmopolitanism, Levinas and Buber’s otherness, Derrida’s hospitality and Taylor’s multiculturalism, with the aim to evaluate the limitations of each perspective and settle the institution of refuge as an exigence of humanity. With this, this search seeks, in these new theoretical and philosophical bases, the justification of normative processes for the regulation of models of citizenship that transcend national parameters, for a plural accommodation of contemporary diasporas.